2022
DOI: 10.1186/s12885-022-09489-1
|View full text |Cite
|
Sign up to set email alerts
|

Humanized CD19 CAR-T cells in relapsed/refractory B-ALL patients who relapsed after or failed murine CD19 CAR-T therapy

Abstract: Background For CD19-positive relapsed/refractory B-cell acute lymphoblastic leukemia (r/r B-ALL) after treatment with murine CD19 (mCD19) CAR-T, the reinfusion of mCD19 CAR-T cells may be ineffective due to anti-mouse single-chain variable fragment (scFv) antibody caused by mCD19 CAR. To overcome this immunogenicity, we applied humanized CD19 (hCD19) CAR-T cells to treat r/r B-ALL patients with prior mCD19 CAR-T therapy. Methods Nineteen pediatric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…It was manufactured as described before. 13 Briefly, autologous peripheral blood mononuclear cells (PBMCs) or allogeneic PBMCs apheresed directly from the allo-HSCT donors were stimulated with magnetic beads coated with anti-CD3/CD28 antibodies (Thermo Fisher Scientific) overnight. The next day, transduction via a lentiviral vector was performed at a multiplicity of infection 1:10 ratio.…”
Section: Methodsmentioning
confidence: 99%
“…It was manufactured as described before. 13 Briefly, autologous peripheral blood mononuclear cells (PBMCs) or allogeneic PBMCs apheresed directly from the allo-HSCT donors were stimulated with magnetic beads coated with anti-CD3/CD28 antibodies (Thermo Fisher Scientific) overnight. The next day, transduction via a lentiviral vector was performed at a multiplicity of infection 1:10 ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Myers et al used humanized CD19 CAR-T to treat patients who relapsed after murine-derived CAR-T therapy and reported a 1-month ORR of 64% [ 41 ]. Similarly, An et al observed a CR rate of 68% in their cohort [ 42 ]. Further investigation is needed to determine whether the recurrence in pt01 after CART2 was attributable to anti-murine CAR immunogenicity.…”
Section: Discussionmentioning
confidence: 77%
“…Thus, a combination of these factors might severely impair the treatment outcome among patients with primary refractory DLBCL. Any solution to these problems would be complicated − for example, such patients could be considered for clinical trials with enhanced next-generation CAR-T cell products, which can be rapidly manufactured from the original apheresis for commercial CAR-T cell products ( 16 ). Hence, patients with primary refractory DLBCL without detectable CAR-T cell expansion would be such candidates.…”
Section: Discussionmentioning
confidence: 99%